Improving safety of vulnerable road users: Effectiveness of environment and in-vehicle warning systems at intermodal interchanges. Issue 3 (4th May 2018) - Strawderman, Lesley; King, Katherine; Carruth, Daniel
ABSTRACT: In certain environments pedestrians are at an increased risk for pedestrian-vehicle crashes. Sites such as bus terminals, where there is an increase in foot traffic, create a higher risk for pedestrian injuries and fatalities. The current study investigates the effectiveness of structural and in-vehicle interventions for modifying driver behavior as drivers approach, pass through, and depart from an urban bus terminal. The impact of facility structural elements (pedestrian crossing signs, marked crosswalks, and sidewalks) and an in-vehicle pedestrian warning system was evaluated using the Center for Advanced Vehicular Systems driving simulator. Thirty-seven participants completed an urban driving task in a high-fidelity driving simulator. Driver speed and lane position were evaluated. An in-vehicle alarm indicating "high pedestrian areas" led to reduced driver speed, but drivers shifted closer to the shoulder (and pedestrians). Marked crosswalks had no observed effect on driver speed or vehicle controls but also led to drivers positioning themselves closer to the shoulder. Drivers exhibited risk-compensation behaviors by driving faster and closer to shoulders when sidewalks were present. Pedestrian crossing signals led to reduced driver speed. The authors recommend the placement of signed crosswalks mid-street where there is high pedestrian traffic.